2020
DOI: 10.1097/md.0000000000021278
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal endoscopy nurse assistance during colonoscopy and polyp detection

Abstract: Background: Previous studies showed difference results about the effect of nurse in improvement of the colonoscopy detection rate. This meta-analysis aims to investigate whether nurse participation during colonoscopy can help in improving the detection rate of polyps and adenomas. Methods: Original studies in English were searched from the MEDLINE database, PubMed, Web of Science, and the Cochrane Library database. Randomized control trials (RCT) comparing colonoscopy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A retrospective study by Lei and colleagues also aimed to investigate the performance of computer-aided diagnosis in colonoscopy and found no difference in ADR in the morning or in the afternoon [11] in patients who were investigated with AI. However, the authors did not include colonoscopies without the use of AI into their analysis as comparators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study by Lei and colleagues also aimed to investigate the performance of computer-aided diagnosis in colonoscopy and found no difference in ADR in the morning or in the afternoon [11] in patients who were investigated with AI. However, the authors did not include colonoscopies without the use of AI into their analysis as comparators.…”
Section: Discussionmentioning
confidence: 99%
“…The use of AI systems may have a similar effect as having additional investigators in the room, as shown by several studies. A meta-analysis clearly demonstrated that the participation of nurses in the detection of polyps of adenoma increased the ADR and PDR significantly [11].…”
Section: Discussionmentioning
confidence: 99%
“…[109][110][111][112] A metaanalysis of these trials including 2268 patients demonstrated that assignment of nurses to observe the colonic inspection was associated with significantly increased adenoma detection (RR, 1.19; 95% CI, 1.07-1.32) and nonsignificantly increased advanced lesion detection (RR, 1.33; 95% CI, .95-1.87). 113 These studies suggest that colonoscopists should not only endeavor to retain experienced endoscopy nurses, but they should also encourage endoscopy room staff to participate in the inspection of the colonic mucosa whenever not otherwise occupied with their role in monitoring of the patient and assisting with the procedure.…”
Section: Interventions (Facility Level Provider Level)mentioning
confidence: 99%
“…There have been several experimental trials aimed at reducing the false-negative results in adenoma detection on colonoscopy. One study reported that an appropriate with-194 DOI: 10.1159/000528085 drawal technique is useful for decreasing the adenoma miss rate (AMR), whereas another suggested that the rate of false-negative results can be reduced by having a nurse or another doctor look at the endoscope screen during the examination [3,4]. However, although the support of nurses and doctors is considered to be highly effective, their participation in the diagnostic process is limited by the lack of adequate legal regulations.…”
Section: Introductionmentioning
confidence: 99%